Kemampuan koneksi matematis siswa SMP ditinjau dari faktor gender - Farhan Nurul Imam; Darhim Darhim (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
The ability to connect mathematically is one of the abilities that need to be possessed and developed at the high school level because it can make students relate mathematics to everyday life. This study aims to describe the mathematical connection ability of junior high school students in terms of gender factors. This research uses qualitative methods. The subjects of the study used the method of sampling techniques. Of the 10 classes, 1 class will be taken with the criteria of one class with a good average math score and another 6 students with 3 boys and 3 girls with the criteria of having good mathematical skills to obtain more in-depth information. The stages of research are (1) providing math test questions to build a flat side room (2) describe students' connection abilities based on the results of answer sheets and subject interviews, (3) triangulate with in-depth interviews (Indept Interviews) in a structured and open format, and (4) infer students' mathematical connection abilities in solving flat-sided space building problems based on subjects and interview answer sheets. The results of this study showed that male and female students have high mathematical connection skills.